Biochemical investigation of multicorer sediment profile PS85/469-2 - Schewe, Ingo (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2019)
To detect and track the impact of large-scale environmental changes in a the transition zone between the northern North Atlantic and the central Arctic Ocean, and to determine experimentally the factors controlling deep-sea biodiversity, the Alfred- Wegener-Institute for Polar and Marine Research (AWI) established the deep-sea long-term observatory HAUSGARTEN, which constitutes the first, and until now only open-ocean long-term station in a polar region. Virtually undisturbed sediment samples have been taken using a video-guided multiple corer (MUC) at 13 HAUSGARTEN stations along a bathymetric (1,000 - 4,000 m water depth) and a latitudinal transect in 2,500 m water depth as well as two stations at 230 and 1,200 m water depth within the framework of the KONGHAU project. Various biogenic sediment compounds were analyzed to estimate the input of organic matter from phytodetritus sedimentation, benthic activities (e.g. bacterial exoenzymatic activity), and the total biomass of the smallest sediment-inhabiting organisms (size range: bacteria to meiofauna).